Pengaruh Pengetahuan Dan Lingkungan Sosial Terhadap Job Preference Pada Alumni Perbankan Syariah FEBI UINSU - Ritonga, Rabiatul Hadawiyah; Rokan, Mustapa Khamal; Irham, Mawaddah (Universitas Labuhanbatu, 2023)
In choosing a job (job preference) every human being has the right to choose each according to what he wants. However, to form this order, certain factors are needed which are considered important in determining which profession to choose. These factors are knowledge and the social environment related to the desired job. Statistical data states that none of the Islamic banking graduates work in Islamic banking, and there are even Islamic banking graduates who work in conventional banks. Therefore, graduating students need to have knowledge and a social environment in the career field they are interested in so that it can encourage them to choose a career (job preference). This study aims to determine the effect of knowledge and the social environment on job preference in UINSU FEBI graduates. The method used in this study was a quantitative method using 121 respondents taken from FEBI UINSU graduates in 2018 and 2019. The data in this study were collected using a questionnaire which had previously been tested for validity and reliability. The data analysis used was Multiple Linear Regression Analysis which was tested using IBM SPSS Statistic 26 Software. The results showed that Knowledge had an effect on Job Preference in Islamic Banking graduates FEBI UINSU, Social Environment had an effect on Job Preference in Islamic Banking graduates FEBI UINSU, Knowledge and The social environment simultaneously influences Job Preference for Islamic Banking graduates of FEBI UINSU.